KONTESTASI NEGARA, AGAMA MAYORITAS DAN HAK ASASI MANUSIA (HAM) DALAM PERATURAN DAERAH BERNUANSA SYARIAH - Mirza Satria Buana; Ellisa Vikalista (Arena Hukum, 2019)
AbstractThis paper aims to scrutinize the issue relating to the relationship between state and religion which tend to be problematic. Religion is believed to be one of the most important moral-transcendental forces in society. However, in the setting of modern world, the government is also required to carry out its administrative activities in a neutral, non-discriminatory manner and free from certain religious majority biases. In other words, the government can neither privilege one religion, especially the majority one nor discriminate the minority one. This is a socio-legal research which addresses problems through inter-disciplinary approaches. Libertarian political theories will be presented to complement legal and human rights theories related to religious and state relations. The texts in the legislation are seen through their socio-political meaning and purpose by pre-text-text-context analysis. This writing offers secularity options which are inclusive models of secularism. Ideally, the state is in a neutral position in public space, where the state may not be too active in regulating the religious aspects of the majority religion, except in the ihktiar to maintain legal pluralism and affirmative action for vulnerable groups. AbstrakTulisan ini bertujuan untuk mengurai permasalahan terkait relasi agama dengan negara yang cenderung problematik. Agama dipercaya sebagai salah satu kekuatan moral-transendental penting dalam bermasyarakat, namun pemerintah juga dituntut untuk menjalankan kegiatan administratifnya secara netral, non-diskriminatif dan terbebas dari bias mayoritas keagamaan tertentu. Pendekatan penelitian yang digunakan adalah socio-legal yang mencandra permasalahan lewat pendekatan inter-disipliner; teori-teori politik libertarian akan dipaparkan untuk melengkapi teori-teori hukum dan HAM terkait relasi agama dan negara. Teks-teks dalam perundang-undangan dicari makna dan tujuan sosio-politiknya, lewat analisa pre-text – text – context.Tulisan ini menawarkan opsi sekularitas yang merupakan model inklusif dari sekularisme.Idealnya, negara berada dalam posisi netral dalam ruang publik, dimana negara tidak boleh terlalu aktif mengatur aspek-aspek keagamaan pemeluk agama mayoritas, kecuali dalam ihktiar untuk menjaga pluralisme hukum dan affirmative action bagi kalangan rentan.